Belimumab for mucocutaneous manifestations in systemic lupus erythematosus: a systematic review and meta-analysis of trials and pooled post hoc analyses - Abhaya Acharya; Sushant Shah (Annals of Medicine & Surgery, 2026)
Background: Mucocutaneous manifestations affect more than 80% of patients with systemic lupus erythematosus (SLE) and are frequently refractory to standard therapy, contributing to a substantial disease burden. Although belimumab improves overall SLE activity, its specific efficacy in the mucocutaneous domain warrants detailed evaluation. Objective: To evaluate the efficacy of belimumab for mucocutaneous manifestations in patients with active SLE. Methods: Systematic review and meta-analysis of Phase III trials. Quantitative mucocutaneous efficacy data were derived from published pooled individual patient data (IPD) post hoc analyses of these trials (BLISS-52, BLISS-76, BLISS-SC, BLISS-NEA, EMBRACE; N = 3645). Databases (PubMed, Embase, CENTRAL, ClinicalTrials.gov) were searched through December 2025. The primary outcome was the SLE Responder Index-4 (SRI-4) response at week 52. Mucocutaneous outcomes [improvement in mucocutaneous BILAG (mcBILAG) and mucocutaneous SLEDAI-2 K (mcSLEDAI-2 K), sustained improvement, flare prevention, and item-level resolution] were assessed using recent pooled post hoc analyses. Results: Belimumab significantly improved SRI-4 response [pooled odds ratio (OR), 1.58; 95% confidence interval (CI), 1.36–1.83; P < 0.00001]. In patients with baseline mucocutaneous involvement, belimumab was superior to placebo in inducing mcBILAG improvement (OR, 1.29; 95% CI, 1.07–1.57), mcSLEDAI-2 K improvement (OR, 1.37; 95% CI, 1.16–1.62), and sustained mcBILAG response [hazard ratio (HR), 1.23; 95% CI, 1.07–1.41]. Greater benefits were observed in subgroups with high baseline disease activity (SLEDAI-2 K 10) or serological activity (positive anti-dsDNA). Item-level resolution favored belimumab for rash, alopecia, and mucosal ulcers. Conclusion: Belimumab, added to standard therapy, significantly enhances global SLE control and provides consistent, sustained improvement in mucocutaneous manifestations, particularly in patients with higher disease activity or serological positivity. These data support belimumab as an effective option for refractory mucocutaneous SLE.